Efficacy of abobotulinumtoxinA versus onabotulinumtoxinA for the treatment of refractory neurogenic detrusor overactivity: a systematic review and indirect treatment comparison. (31st December 2023) - Cruz, Francisco; Danchenko, Natalya; Fahrbach, Kyle; Freitag, Andreas; Tarpey, Jialu; Whalen, John
Abstract: Aims: To compare the efficacy and safety of abobotulinumtoxinA (aboBoNT-A) and onabotulinumtoxinA (onaBoNT-A) for the treatment of refractory neurogenic detrusor overactivity (NDO), using an indirect treatment comparison (ITC). Materials and methods: A systematic literature review was used to identify randomized controlled trials (RCTs) that evaluated botulinum toxin type A for the treatment of refractory NDO. Treatments were compared using a Bucher ITC approach. Efficacy outcomes were reduction in number of weekly urinary incontinence (UI) episodes at 6, 12, and 24 weeks of follow-up. The safety outcome was the proportion of patients with treatment-emergent urinary tract infections (TE-UTIs) during follow-up. Subgroup/sensitivity analyses were performed to investigate the impact of heterogeneity. Results: Fifteen studies of botulinum toxin type A were identified. Among these, onaBoNT-A 200 U was the only botulinum toxin type A considered an appropriate comparator for aboBoNT-A 600 U and 800 U. As such, six RCTs that evaluated onaBoNT-A or aboBoNT-A were included in the ITC. In base-case analyses, there were no statistically significant differences between aboBoNT-A and onaBoNT-A in terms of UI episodes or TE-UTIs. Numerically, the trend favored aboBoNT-A (either dose) for all endpoints and time points. At 12 and 24 weeks, the difference in reduction of UI episodes per week was considered clinically relevant when comparing aboBoNT-A 800 U with onaBoNT-A 200 U, but not when comparing the lower dose of aboBoNT-A (600 U) with onaBoNT-A 200 U. Results from subgroup/sensitivity analyses were consistent with the base case. Limitations: Heterogeneity across studies was observed; however, strong consistency of trends across analyses suggests the impact of heterogeneity is low. Conclusions: There may be potential advantages of aboBoNT-A over onaBoNT-A, in terms of UI reduction, in patients with refractory NDO. More confirmatory studies are needed owing to the sparsity of current evidence. PLAIN LANGUAGE SUMMARY: Neurogenic detrusor overactivity (NDO) is a condition in which the bladder muscle wall is overactive and does not function normally. This can lead to urinary incontinence (i.e. accidental leakage of urine). NDO may also cause urinary tract infections and upper urinary tract damage if it is left untreated or if treatment does not work (i.e. refractory NDO). Botulinum toxin is a treatment that relaxes muscles in patients with refractory NDO, so they have less chance of experiencing urinary incontinence. This study used results from clinical trials to compare two types of botulinum toxin – abobotulinumtoxinA (aboBoNT-A) and onabotulinumtoxinA (onaBoNT-A) – to see if one works better than the other. Clinical trials are experiments to assess how well treatments work by giving different treatments to different patients and observing the results. When there is no clinical trial that compares the two treatments you are interested in, it is possible to combine results from a number of different clinical trials instead. This is known as an indirect treatment comparison. We used an indirect treatment comparison to compare aboBoNT-A and onaBoNT-A for the treatment of refractory NDO. Results showed that aboBoNT-A may be more effective than onaBoNT-A in reducing the frequency of urinary incontinence episodes. On average, patients treated with aboBoNT-A had at least three fewer episodes of urinary incontinence per week than those treated with onaBoNT-A. These results suggest that patients treated with aboBoNT-A could have a better quality of life than those treated with onaBoNT-A.